Carbon Footprint Assessment of Local Administrative Office: A Case Study of Bannang Sata Subdistrict Administrative Organization, Yala Province - Phantaweesub, Narumol; Cheseng, Arif; Muadchim, Maytiya; Chesoh, Hafsah (YRU Journal of Science and Technology, 2025)
Natural disasters are becoming increasingly severe, primarily due to human-induced greenhouse gas emissions, causing significant impacts on life and property. This study aimed to assess the carbon footprint and propose strategies to reduce greenhouse gas emissions of the Bannang Sata Subdistrict Administrative Organization, Yala Province. The assessment was conducted across three scopes, with refrigerant leakage of R-22 considered separately, following the guidelines of the Thailand Greenhouse Gas Management Organization, and data were collected from January to December 2023. The total carbon footprint was 51.42 tCO2e, with electricity consumption in Scope 2 contributing the most 41.87 tCO2e (81.39%), followed by Scope 1 8.69 tCO2e (16.90%) and Scope 3 0.86 tCO2e (1.71%). Refrigerant leakage of R-22 accounted for 152.41 tCO2e (74.76% of all activities). Replacing conventional lighting with LED bulbs could reduce the organization’s greenhouse gas emissions by 49%, with a payback period of 10 months. Installing rooftop solar panels was identified as a cost-effective long-term investment. Additionally, switching the refrigerant to R-32 could save up to 48.89 kWh per year, or alternatively using R-290, which has comparable efficiency but a global warming potential (GWP) 550 times lower than the original refrigerant. Establishing a data recording system and expanding assessment activities to align with evaluation guidelines can enable the organization to assess its carbon footprint more effectively, supporting the achievement of future greenhouse gas emission reduction targets.